Analytical Inversion of Tridiagonal Hermitian Matrices - Hakopian, Yuri R.; Manukyan, Avetik H. (Mathematical Problems of Computer Science, 2022)
In this paper we give an algorithm for inverting complex tridiagonal Hermitian matrices with optimal computational efforts. For matrices of a special form and, in particular, for Toeplitz matrices, the derived formulas lead to closed-form expressions for the elements of inverse matrices.